Exploring the Mechanism of Action of the "Scutellaria Barbata D.Don-Prunella Vulgaris L." Herb Pair in the Treatment of Lung Cancer Using Network Pharmacology and Molecular Docking Techniques - Liu, Hongzhi; Han, Le (Journal of Contemporary Medical Practice, 2024)
Objective: To explore the mechanism of action of the herbal pair "Scutellaria barbata D.Don-Prunella vulgaris L." in the treatment of lung cancer through network pharmacology and molecular docking techniques. Methods: Active ingredients and their targets of Scutellaria barbata D.Don and Prunella vulgaris L. were collected and screened from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP). Disease-related targets were obtained and screened from the Genecards and OMIM databases. The intersection Venn diagram of the targets of "Scutellaria barbata D.Don-Prunella vulgaris L." and lung cancer disease targets was obtained using R 4.4.1 software and packages such as "ggvenn". A drug-active ingredient-target-disease association network was constructed in Cytoscape 3.10.0, and core active ingredients were screened using the Analyze Network function. A PPI network for drug-disease common targets was constructed using the String database website, and the TSV format of protein interaction relationship files was imported into Cytoscape 3.10.0 software,install and run CytoHubba to calculate and obtain the core targets in the network. GO function and KEGG pathway enrichment analyses were performed on drug-disease common targets using R 4.4.1 software. Finally, molecular docking validation was performed on core ingredients and core targets using AutoDock, and the three best binding molecular docking patterns were displayed using PyMol software. Results: A total of 33 active drug components and 108 drug-disease common targets were obtained. Among them, there are 5 core active components: quercetin, luteolin, wogonin, kaempferol, and baicalein; core targets include TP53, AKT1, JUN, HSP90AA1, etc. GO analysis yielded 2, 010 related entries. KEGG analysis identified 147 signaling pathways. Molecular docking showed that the core active components have strong affinity with the core targets. Conclusion: The drug pair of Scutellaria barbata D.Don and Prunella vulgaris L. may exert anti-tumor effects by acting on targets such as TP53, AKT1, JUN, HSP90AA1, and through signaling pathways like PI3K-AKT, inhibiting tumor cell proliferation, promoting tumor cell apoptosis, suppressing its proliferation, differentiation, and metastasis, thereby achieving therapeutic effects on lung cancer.